Effects of feeding pattern on growth, immunity and intestinal flora of GIFT tilapia (Oreochromis niloticus) and largemouth bass (Micropterus salmoides) - Yuning Wang; Rui Wang; Ruiyi Yang; Shaoyu Zhu; Feng Yao; Xiaohua Zhang; Yanou Yang (Aquaculture Reports)
The omnivorous GIFT tilapia (Genetically Improved Farmed Tilapia (Oreochromis niloticus)) and carnivorous largemouth bass (Micropterus salmoides) were fed in four feeding patterns to compare the compensatory growth for fish species with different feeding habits. These patterns included satiation (control, fed twice a day at satiation), fasting 2 d and re-feeding 8 d and cycling (the daily feeding pattern is the same as that of the control group, the same below), fasting 4 d and re-feeding 16 d and cycling (both cyclical fasting), feeding once every 10 d then 10 d on satiation and cycling (cyclical food restriction), and each pattern is 60 d. The results showed that both fish species failed to obtain compensatory growth during the cyclical fasting. However, both species obtained completely compensatory growth by significantly improving actual feeding rate and feed efficiency ratio during the cyclical food restriction. During the feeding pattern, GIFT tilapia had significantly higher amylase activity, liver and muscle glycogen contents, and significantly lower blood glucose and serum insulin contents. Largemouth bass had significantly higher protease and lipase activities, and lower blood glucose content. Both species had significantly lower relative expression levels of pro-inflammatory factors in livers; GIFT tilapia had significantly lower and largemouth bass had significantly higher anti-inflammatory factors. Furthermore, GIFT tilapia had significantly higher relative abundance of harmful bacteria and lower relative abundance of beneficial bacteria, and intestinal immunity was impaired; largemouth bass changed the opposite, and intestinal immunity was improved. The results suggest that GIFT tilapia improved their carbohydrate utilization efficiency and largemouth bass improved their protein utilization efficiency, in cyclical food restriction, and the two species achieved completely compensatory growth, but GIFT tilapia impaired immunity, and largemouth bass improved immunity.